SPLEEN INJURY IN THE STRUCTURE OF COMBINED LETHAL TRAUMA IN CHILDREN - I. A. Pikalo (Acta Biomedica Scientifica, 2012)
According to the retrospective analysis of combined lethal trauma in 105 children, the frequency of spleen trauma is 31,4 %. The risk of death, from intraabdominal bleeding at the spleen trauma is very low (OR = 0,16; 95% CI 0,019-1,34; p = 0,04). At the spleen trauma the volume of hemothorax considerably exceeded the volume of hemoperitoneum (977 ± 866,9 ml vs 311 ± 270,3 ml; p < 0,0003). The risk of death from the bleeding in thoracic cavity 45 times higher than the one from bleeding in abdominal cavity. The degree of spleen injury in children has low correlation with, trauma mechanism (r = 0,17; p < 0,37) and with the volume of hemoperitoneum (r = 0,1; p < 0,5). The probability of death from injury at the scene is low (OR = 0,09; 95% CI 0,0096-0,84; p < 0,017). The main causes of children's death, at the combined injury are cranial trauma, hemorrhagic shock at thoracic trauma and. traumatic shock.